Pendekatan Pastoral Berdasarkan Metafora Alkitabiah: 'Gembalakanlah Kawanan Domba Allah' - Tambun, Roy Haries Ifraldo; Raulina, Raulina (Jurnal Teologi dan Pelayanan Kerusso, 2023)
This study discusses a pastoral approach based on the biblical metaphor "Shepherd the Flock of God" (1 Peter 5:2). This metaphor serves as a foundation for understanding the role and responsibilities of a church leader in shepherding the congregation. The aim of this research is to identify how the concept of shepherding God's flock can be practically applied in the context of modern pastoral ministry. The method used in this study is a qualitative approach, involving biblical text analysis as well as a literature review related to pastoral roles. Additionally, interviews were conducted with several church leaders to gain contextual insights into the application of this metaphor in daily ministry life. The findings indicate that the metaphor of the "shepherd" depicts a leader who serves with love, patience, and moral responsibility, and who must be able to protect, guide, and nurture their congregation. In conclusion, this metaphor-based pastoral approach emphasizes the importance of a close relationship between church leaders and their congregations, as well as the profound spiritual responsibility involved in nurturing the faith and lives of the members.